Recycling the recyclers: strategies for the immobilisation of a PET-degrading cutinase - Fritzsche, Stefanie; Popp, Marcus; Spälter, Lucas; Bonakdar, Natalie; Vogel, Nicolas; Castiglione, Kathrin (Bioprocess and Biosystems Engineering, 2025)
Enzymatic degradation of polyethylene terephthalate (PET) represents a sustainable approach to reducing plastic waste and protecting fossil resources. The cost efficiency of enzymatic PET degradation processes could be substantially improved by reusing the enzymes. However, conventional immobilisation strategies, such as binding to porous carriers, are challenging as the immobilised enzyme can only interact with the macromolecular solid PET substrate to a limited extent, thus reducing the degradation efficiency. To mitigate this challenge, this work compared different immobilisation strategies of the PET-degrading cutinase ICCGDAQI. Immobilisation approaches included enzyme fixation via linkers to carriers, the synthesis of cross-linked enzyme aggregates with different porosities, and immobilisation on stimulus-responsive polymers. The highest degradation efficiencies were obtained with the pH-responsive material Kollicoat®, where 80% of the initial enzyme activity could be recovered after immobilisation. Degradation of textile PET fibres by the cutinase-Kollicoat® immobilisate was investigated in batch reactions on a 1 L-scale. In three consecutive reaction cycles, the product yield of the released terephthalic acid exceeded 97% in less than 14 h. Even in the fifth cycle, 78% of the maximum yield was achieved in the same reaction time. An advantage of this process is the efficient pH-dependent recovery of the immobilisate after the reaction, which integrates seamlessly into the terephthalic acid recovery by lowering the pH after hydrolysis. This integration therefore not only simplifies the downstream processing, but also provides a cost-effective and resource-efficient solution for both enzyme reuse and product separation after PET degradation, making it a promising approach for industrial application.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Cross-linked enzyme aggregates; Enzymatic depolymerisation; Kollicoat; Plastic waste; Polyethylene terephthalate; Stimulus-responsive polymers